Hormonal Regulation of Hepatic Drug Biotransformation and Transport Systems - Ruiz, Maria Laura (2013)
The human body is constantly exposed to many xenobiotics including environmental pollutants, food additives, therapeutic drugs, etc. The liver is considered the primary site for drug metabolism and elimination pathways, consisting in uptake, phase I and II reactions, and efflux processes, usually acting in this same order. Modulation of biotransformation and disposition of drugs of clinical application has important therapeutic and toxicological implications. We here provide a compilation and analysis of relevant, more recent literature reporting hormonal regulation of hepatic drug biotransformation and transport systems. We provide additional information on the effect of hormones that tentatively explain differences between sexes. A brief discussion on discrepancies between experimental models and species, as well as a link between gender-related differences and the hormonal mechanism explaining such differences, is also presented. Finally, we include a comment on the pathophysiological, toxicological, and pharmacological relevance of these regulations.